Microscopy with ultraviolet surface excitation for rapid slide-free histology. (December 2017) - Fereidouni, Farzad; Harmany, Zachary; Tian, Miao; Todd, Austin; Kintner, John; McPherson, John; Borowsky, Alexander; Bishop, John; Lechpammer, Mirna; Demos, Stavros; Levenson, Richard
Abstract Histological examination of tissues is central to the diagnosis and management of neoplasms and many other diseases and is a foundational technique for preclinical and basic research. However, commonly used bright-field microscopy requires prior preparation of micrometre-thick tissue sections mounted on glass slides—a process that can require hours or days, contributes to cost and delays access to critical information. Here, we introduce a simple, non-destructive slide-free technique that, within minutes, provides high-resolution diagnostic histological images resembling those obtained from conventional haematoxylin and eosin histology. The approach, which we named microscopy with ultraviolet surface excitation (MUSE), can also generate shape and colour-contrast information. MUSE relies on 280 nm ultraviolet light to restrict the excitation of conventional fluorescent stains to tissue surfaces and it has no significant effects on downstream molecular assays (including fluorescence in situ hybridization and RNA sequencing). MUSE promises to improve the speed and efficiency of patient care in both state-of-the-art and low-resource settings and to provide opportunities for rapid histology in research. A slide-free, inexpensive and non-destructive microscopy technique rapidly provides high-resolution histology images that resemble those obtained from conventional haematoxylin-and-eosin-stained specimens.